The impact of a combinatorial digital and organisational intervention on the management of long-term conditions in UK primary care: a non-randomised evaluation - David G. Lugo-Palacios; Jonathan Hammond; Thomas Allen; Sarah Darley; Ruth McDonald; Thomas Blakeman; Peter Bower (BMC, 2019)
Abstract Background Better management of long-term conditions remains a policy priority, with a focus on improving outcomes and reducing use of expensive hospital services. A number of interventions have been tested, but many have failed to show benefit in rigorous comparative research. In 2016, the NHS Test Beds scheme was launched to implement and test interventions combining digital technologies and pathway redesign in routine health care settings, with each intervention comprising multiple innovations to better realise benefit from their 'combinatorial' effect. We present the evaluation of one of the NHS Test Beds, which combined risk stratification algorithms, practice-based quality improvement and health monitoring and coaching to improve management of long-term conditions in a single health economy in the north-west of England. Methods The NHS Test Bed was implemented in one clinical commissioning group in the north-west of England (patient population 235,800 served by 36 general practices). Routine administrative data on hospital use (the primary outcome) and a selection of secondary outcomes (data from both hospital and primary care) were collected in the intervention site, and from a comparator area in the same region. We used difference-in-differences analysis to compare outcomes in the NHS Test Bed area and the comparator after initiation of the combinatorial intervention. Results Tests confirmed the existence of parallel trends in the intervention and comparator sites for hospital outcomes for the period April 2016 to March 2017, and for some of the planned primary care outcomes. Based on 10 months of post-intervention secondary care data and 13 months post-intervention primary care data, we found no significant impact on primary outcomes between the intervention and comparator site, and a significant impact on only one secondary outcome. Conclusion A combinatorial digital and organisational intervention to improve the management of long-term conditions was implemented across a whole health economy, but we found no evidence of a positive impact on health care utilisation outcomes in hospital and primary care.